"Doing Everything on My Own": Examining African American, Latina/o, and Biracial Students' Experiences With School Counselors in Promoting Academic and College Readiness. (December 2021) - Cook, Amy L.; Hayden, Laura A.; Tyrrell, Rachel; McCann, Arthur G.
We examined the high school experiences of 133 African American, Latina/o, and biracial college students through employing a mixed methods concurrent nested design, including survey analysis and qualitative content analysis, to identify themes and the extent school counselors provided assistance with promoting academic and college readiness. The American School Counselor Association (ASCA) National Model and Multicultural and Social Justice Counseling Competencies (MSJCC) were used as a conceptual framework to guide the study. Findings included the need for greater support from school counselors, to strengthen collaborative efforts across school community members and access to academic resources. Implications for counseling practice in urban schools are provided.